2018
DOI: 10.1038/s12276-018-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

ATP depletion during mitotic arrest induces mitotic slippage and APC/CCdh1-dependent cyclin B1 degradation

Abstract: ATP depletion inhibits cell cycle progression, especially during the G1 phase and the G2 to M transition. However, the effect of ATP depletion on mitotic progression remains unclear. We observed that the reduction of ATP after prometaphase by simultaneous treatment with 2-deoxyglucose and NaN3 did not arrest mitotic progression. Interestingly, ATP depletion during nocodazole-induced prometaphase arrest resulted in mitotic slippage, as indicated by a reduction in mitotic cells, APC/C-dependent degradation of cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…Consistent with this, mitotic slippage was induced when taxol-treated cells were exposed to heat shock (61), implying that heat shock can attenuate SAC activation. Very recently, it was reported that ATP depletion induces mitotic slippage via APC/C-dependent cyclin B1 degradation (62). Given that ATP levels are reduced during heat stress (16,58,59), heat shock-induced attenuation of the 0.01 mg/ml taxol for 24 h and monitored by time-lapse imaging during the second half of the taxol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, mitotic slippage was induced when taxol-treated cells were exposed to heat shock (61), implying that heat shock can attenuate SAC activation. Very recently, it was reported that ATP depletion induces mitotic slippage via APC/C-dependent cyclin B1 degradation (62). Given that ATP levels are reduced during heat stress (16,58,59), heat shock-induced attenuation of the 0.01 mg/ml taxol for 24 h and monitored by time-lapse imaging during the second half of the taxol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, mitotic slippage may occur prematurely without accurate chromosomal segregation or cytokinesis [39]. The rate of mitotic slippage is positively correlated to the rate of cyclin B1 ubiquitination and degradation in active SAC condition [40,41]. Numerous studies have documented that mitotic slippage can limit the effectiveness of microtubule poisons [42].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Drp1 promotes mitotic exit (adaptation) of cells arrested in mitosis with the microtubule-stabilizing drug taxol via regulation of Cyclin B1 levels [78] . Similarly, ATP depletion by addition of 2-deoxy-glucose (2-DG) and sodium azide promotes mitotic exit in cells arrested in mitosis with the microtubule depolymerizing drug nocodazole, and this adaptation is also due to reduction in Cyclin B levels [79] . These results indicate a bi-directional crosstalk where the mitotic machinery increases Drp1 activity and mitochondria dynamics in mitosis, which in turn feedbacks to regulate mitosis [80] .…”
Section: Mitochondria Dynamics Are Regulated By the Cell Cyclementioning
confidence: 99%
“…Other metabolic alterations such as starvation and the subsequent induction of autophagy, or hypoxia have also been shown to regulate cell cycle progression [97] . Mitochondria dynamics/function have a role in the regulation of mitosis since Drp1 activity and ATP depletion promote mitotic exit in cells arrested in mitosis with microtubule-targeting drugs [78,79] . This exit from mitotic arrest when mitochondria function is compromised is due to premature degradation of Cyclin B1 by activation of the ubiquitin ligase APC/C Cdh1 [79] .…”
Section: The Cell Cycle Is In Turn Regulated By Mitochondria Functionmentioning
confidence: 99%
See 1 more Smart Citation